THE JEWS CENTERS OF MANUFACTURES OF TEXTILE IN GALICIA AT THE END OF ХІХ – THE FIRST THIRD OF ХХ CENTURY: TRENDS, ASSORTMENT - Козакевич, О. Р. (Art and Design, 2020)
Textile manufacturing owned by the Jews in Galicia at the end of ХІХ – the first third of XX century is studied in the article. On the basis of archive documents and author’s field materials, preconditions for establishing relevant centers are determined; the main factors that influenced the textile industry development are highlighted. The attention is focused on knitted and lace goods manufacturing of both new and fancy assortment of the period under the study. The principle of a systematic approach and complex study constitutes the methodological basis. In order to investigate the selected object of study, historical and art studies methods are applied. During the scientific expeditions while collecting materials from the old inhabitants the interview method was used. Textile manufacturing in Galicia is divided into two main directions: according to the manufacturing principle: folk textile, where centuries-old traditions prevail, and professional textile, where specialists and special-purpose equipment are involved and fashionable trends are considered. It was found that at the end of ХІХ – the first third of XX century a considerable part of local textile industry was owned by the Jews. To some extent, this was due to the fact that they received proper education, set up own businesses, produced assortment that met the demands of consumers of various strata of society. Knitted and lace goods manufacturing, which became fashionable both in urban and rural areas, was productive. It was ascertained that apart from fancy goods, traditional woven Hutsul «zapaska», carpets and «kraikas» involving local population were manufactured. The scientific novelty consists in the study of one more aspect of textile industry in Galicia where the attention is focused on the peculiarities of manufacturing the textile assortment in the centers belonging to the Jews. The study allows expanding knowledge of textile industry in Galicia, clothes assortment and interior fabrics manufacturing centers, which favours involving the received data to learn the history of textile in Galicia.